The one true love of Alice-Ann [large type] - Everson, Eva Marie (Thorndike Press, a part of Gale, a Cengage Company, 2017)
Living in rural Georgia in 1941, sixteen-year-old Alice-Ann has her heart set on her brother's twenty-one-year-old friend Mack. Alice-Ann knows she can make Mack see her for the woman she'll become. But when they receive news of the attack on Pearl Harbor and Mack decides to enlist, Alice-Ann realizes she must declare her love before he leaves. Though promising to write, Mack leaves without confirmation that her love is returned. But Alice-Ann is determined to wear the wedding dress her maiden aunt never had a chance to wear -- having lost her fiancé in the Great War. As their correspondence continues over the next three years, Mack and Alice-Ann are drawn closer together. But then Mack's letters cease altogether, leaving Alice-Ann to fear history repeating itself. Dreading the war will leave her with a beautiful dress and no happily ever after, Alice-Ann fills her days with work and caring for her best friend's war-torn brother, Carlton. As time passes and their friendship develops into something more, Alice-Ann wonders if she'll ever be prepared to say good-bye to her one true love and embrace the future God has in store with a newfound love. Or will a sudden call from overseas change everything?